On the impingement of heat transfer using swirled air jets - Kotb, Ashraf; Askar, Hamada; Saad, Hany (Frontiers in Mechanical Engineering, 2023)
Experimental analyses were conducted under identical experimental conditions on the heat transfer between a constant heat flux flat plate and a round air jet for both conventional and swirled jets. Vane-type swirl generators inserted at the nozzle exit were used to produce a swirl. The experimental measurements were performed at a fixed Reynolds number value (Re = 23,000) calculated on the jet tube’s inside diameter. A comparison between conventional air jets and swirl jets with swirl numbers of S = 0, 0.19, 0.42, and 0.72 was presented for the different nozzle-to-plate spacings Z/D = 2, 6, and 10. The results show that heat transfer to the plate decreases when the nozzle-to-plate distance increases. In addition, increasing the swirl number S increases heat transfer uniformity but decreases global heat transfer. At the low plate-to-jet distance Z/D = 2, the point of maximum heat transfer is shifted to a radial position depending on the swirl number. Also, for both Z/D = 6 and 10, the stagnation point and stagnation region heat-transfer enhances only for swirl numbers 0 and 0.19.